Mothering as a Life Course Transition: Do Women Go Straight for Their Children? - Michalsen, Venezia (Journal of Offender Rehabilitation, 2011)
In this study, qualitative, in-depth interviews were conducted with 100 formerly incarcerated mothers to explore the relationship between attachment to children and desistance from criminal behavior. Exploratory data analysis revealed that mothers do believe that children play important roles in their desistance, consistent with the tenets of life course theory. However, children were also described as sources of great stress, which may in turn promote criminal behavior. Women also related desistance to reliance on self and a higher power, and to a desire to avoid future involvement with the criminal justice system. The article concludes with a call for more research on women's desistance, and increased consideration of parent–child relationships in corrections policy decision making.
_eprint: https://doi.org/10.1080/10509674.2011.589887
Keywords: attachment; children; dept.soc; desistance; life course theory; mothers; peer-reviewed; reentry

Curriculum Innovation Program Fellowship "Serving the Community Through Service Learning" - Jackson, Shirley A. (2011)
Dr. Jackson worked on her Curriculum Innovation Program fellowship, "Serving the community through service learning," completed write-up for Ethnic Studies Curriculum-Related Activity Grant for "Ethnic Studies Program Development at Southern Connecticut State University," worked on several articles and two book proposals encompassing research of race issues and their representation in contemporary cartoons, as well as attended conferences, both as a presenter and a chair, participated in workshops, and reviewed textbook chapters and an article.
Keywords: SCSU; Sabbatical leave report; dept.soc; faculty_collection; sabbatical_report

The Loveless Family: Getting Past Estrangement and Learning How to Love - Bloch, Jon P. (Praeger, 2011)
This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was "dysfunctional" or not., This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was ""dysfunctional"" or not.
Keywords: Families; Psychological aspects; Parenting; Dysfunctional families; Adult children of dysfunctional families; Love; dept.soc; faculty_collection

Backlash 9/11: middle eastern and muslim americans respond - Woods, David W. (Mobilization, 2011)
tex.unique-id: ISI:000292423800012
Keywords: dept.soc; ⛔ No DOI found

Book Review: social order and the fear of crime in contemporary times, by stephen farrall, jonathan jackson, and emily gray. new york, NY: oxford university press, 2009. 319pp. 100.00 cloth. ISBN: 9780199540815 - Adams, Gregory (Contemporary Sociology, 2011)
Citation Key Alias: pop00326 tex.type: [object Object]
Keywords: book.review; dept.soc; ⛔ No DOI found

Social order and the fear of crime in contemporary times - Adams, Gregory (Contemporary Sociology-a Journal of Reviews, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-967-693-481-198 tex.unique-id: [object Object]
Keywords: dept.soc